1996
DOI: 10.1161/01.cir.93.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Comparison of Operator-Specific Outcomes in Interventional Cardiology

Abstract: Background Medical consumers are increasingly requesting methods to discriminate among the results of different providers. Standards for appropriate modeling, risk adjustment, and evaluation (“scorecarding”) in this setting are not well developed, although such evaluation is being performed by the medical insurance industry and by several states in the United States. Our objectives were to develop and examine clinically meaningful methodology for assessing the operator-specific results for percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…A n inverse relationship between both physician and hospital PTCA volumes and adverse outcomes has been demonstrated in numerous studies [1][2][3][4][5][6][7][8][9][10][11][12] involving thousands of patients undergoing predominantly elective procedures. It is not known whether a distinct volume-outcome relation exists for PTCA performed as primary reperfusion therapy for acute myocardial infarction (AMI) (primary angioplasty).…”
mentioning
confidence: 99%
“…A n inverse relationship between both physician and hospital PTCA volumes and adverse outcomes has been demonstrated in numerous studies [1][2][3][4][5][6][7][8][9][10][11][12] involving thousands of patients undergoing predominantly elective procedures. It is not known whether a distinct volume-outcome relation exists for PTCA performed as primary reperfusion therapy for acute myocardial infarction (AMI) (primary angioplasty).…”
mentioning
confidence: 99%
“…The author of this study concluded that given these improvements, lower minimum volume standards might be justifiable in less populated areas, where the alternative is no access to angioplasty at all. Importantly, procedural volume is only one of many factors contributing to the variability of measured outcomes (58,82,89). Furthermore, there is no clear "cut-off " above or below which hospitals, or groups of hospitals in aggregate, perform well or poorly.…”
Section: Relationship Of Institutional Volume To Procedural Outcomementioning
confidence: 99%
“…There are statistical associations between activity levels and short-term complication rates (emergency CABG and mortality) (17,58,85,89,97,101) for both institutions and for individual operators. In particular, low-volume operators operating at low-volume hospitals had an increased mortality rate.…”
Section: Volume-activity Relationshipsmentioning
confidence: 99%
“…12 A number of studies have shown that lean patients (<20 kg/m 2 ) and those with normal BMI (20-24.9 kg/m 2 ) are at a higher risk for adverse in-hospital outcomes and post-PCI complications than overweight (25-29.9 kg/m 2 ) and obese (≥30 kg/m 2 ) patients. [12][13][14] . This unexpected phenomenon was explained by "obesity paradox".…”
Section: Introductionmentioning
confidence: 99%